Strain Rate‐Dependent Hardening‐Softening Characteristics of Gas Hydrate‐Bearing Sediments. (8th November 2019) - Deusner, C.; Gupta, S.; Xie, X.‐G.; Leung, Y. F.; Uchida, S.; Kossel, E.; Haeckel, M.
Abstract: The presence of gas hydrates (GHs) increases the stiffness and strength of marine sediments. In elasto‐plastic constitutive models, it is common to consider GH saturation ( S h ) as key internal variable for defining the contribution of GHs to composite soil mechanical behavior. However, the stress‐strain behavior of GH‐bearing sediments (GHBS) also depends on the microscale distribution of GH and on GH‐sediment fabrics. A thorough analysis of GHBS is difficult, because there is no unique relation between Sh and GH morphology. To improve the understanding of stress‐strain behavior of GHBS in terms of established soil models, this study summarizes results from triaxial compression tests with different S h, pore fluids, effective confining stresses, and strain histories. Our data indicate that the mechanical behavior of GHBS strongly depends on S h and GH morphology, and also on the strain‐induced alteration of GH‐sediment fabrics. Hardening‐softening characteristics of GHBS are strain rate‐dependent, which suggests that GH‐sediment fabrics dynamically rearrange during plastic yielding events. We hypothesize that rearrangement of GH‐sediment fabrics, through viscous deformation or transient dissociation and reformation of GHs, results in kinematic hardening, suppressed softening, and secondary strength recovery, which could potentially mitigate or counteract large‐strain failure events. For constitutive modeling approaches, we suggest that strain rate‐dependent micromechanical effects from alterations of the GH‐sediment fabrics can be lumped into a nonconstant residual friction parameter. We propose simple empirical evolution functions for the mechanical properties and calibrate the model parameters against the experimental data. Plain Language Summary: Gas hydrates (GHs) are crystalline‐like solids, which are formed from natural gas molecules and water at high pressure and low temperature. GHs, and particularly methane hydrates, are naturally abundant in marine sediments. It is known that the presence of GH increases the mechanical stiffness and strength of sediments, and there is strong effort in analyzing and quantifying these effects in order to understand potential risks of sediment destabilization or slope failure. Based on our experimental results from high‐pressure geotechnical studies, we show that not only the initial amount and distribution of GH are important for the increased strength of GH‐bearing sediments but also the dynamic rearrangement of GH‐sediment fabrics during deformation characterizes the stress‐strain response and enables strength recovery after failure. We propose that different microstructural mechanisms contribute to this rearrangement and strength recovery of GH sediment. However, we consider these complicated processes in a simplified manner in an improved numerical model, which can be applied for geotechnical risk assessment on larger scales. Key Points: The mechanical properties and hardening‐softening characteristics of gas hydrate‐bearing sediments are dependent on strain rates Hardening‐softening behavior and strength evolution depend on structural alterations and dynamic rearrangement of gas hydrate‐sediment fabrics The effects of strain rate‐dependent structural alterations can be conceptualized as a nonconstant residual friction term in soil mechanical modeling